WIC Participation and Relative Quality of Household Food Purchases: Evidence from FoodAPS. (26th April 2019) - Fang, Di; Thomsen, Michael R.; Nayga, Rodolfo M.; Novotny, Aaron M.
Abstract : We examine the effect of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) on the quality of household food purchases using the National Household Food Acquisition and Purchase Survey (FoodAPS) and propensity score matching. A healthy purchasing index (HPI) is used to measure nutritional quality of household food purchases. WIC foods explain the improvement in quality of food purchases, not self‐selection of more nutrition‐conscious households into the program. The improvement in purchase quality was driven entirely by WIC participating households who redeemed WIC foods during the interview week. There was no significant difference between WIC participants who did not redeem WIC foods and eligible nonparticipants. In this sample, there is no evidence that lack of access to clinics has adverse effects on participation nor is there evidence that HPI depends on supermarket access. A supervised machine learning process supports our main conclusion on the importance of WIC foods.